Atividade antioxidante e hepatoprotetora de chalconas sintéticas em modelos experimentais in vitro e ex vivo - Silva, Jadyellen Rondon e (2022)
The relationship between oxidative stress and various pathologies has increased the search for antioxidant compounds. Chalcones have several biological activities and the interest in this class of molecules is growing due to their versatile structure, allowing their modification to potentiate their activities and assign more than one activity to the same molecule. In this work we initially evaluated the in vitro antioxidant activity of functionalized synthetic chalcones (1-100 μM) against iron-induced lipid peroxidation in different animal tissues. Chalcone E showed more promise against lipid peroxidation, so it was selected for the DPPH radical scavenging activity test. Subsequently, chalcone E was evaluated in an ex vivo model of liver injury and oxidative damage induced by carbon tetrachloride (CCl4) in mice. Chalcone was administered intragastrically at doses of 50 and 100 mg.kg-1 one hour before the intraperitoneal injection of CCl4 (0.1 mL.kg-1 ). Results showed that CCl4 treatment increased aspartate amino transferase (AST) activity in the blood, indicating cellular damage, and decreased plasma levels of triglycerides and total cholesterol, suggesting impaired liver function. In addition, hepatic lipid peroxidation, protein oxidation, non-protein thiol (NPSH) content, catalase and superoxide dismutase activity were also increased by CCl4, revealing changes in oxidative status. Our results demonstrate that chalcone E has an antioxidant potential and its administration prevented the plasma and oxidative changes induced by CCl4, suggesting a hepatoprotective effect, which may be related to its antioxidant action. Despite the promising results, this work did not elucidated the mechanism of action of chalcone E. Its low cytotoxic potential encourages us to carry out further tests in order to further explore the activities of this chalcone and clarify its mechanism of action.